Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.2174/0929867323666160405112019
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vitamin D in Vascular Complications and Vascular Access Outcome in Patients with Chronic Kidney Disease

Abstract: Vitamin D has been known for a long time as a major factor involved in the calcium- phosphate balance and homeostasis, along with parathyroid hormone (PTH). While vitamin D effects on calcium and phosphate are fully known, recent studies attempted to link vitamin D status and cardiovascular diseases. The involvement of vitamin D on vascular remodeling is mediated by several mechanisms such as activation of renin-angiotensin-aldosterone system (RAAS), cell proliferation and anti-apoptotic cell pathways. This co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…Although the underlying mechanistic pathway that might explain the loss of endothelial barrier function in CKD has been unclear so far, it was suggested that vitamin D deficiency might participate in this uremia‐induced phenomenon 6, 32. Here, we found that vitamin D deficiency induced in our recently developed rat model25 did not aggravate the injury on the aortic endothelial layer caused by CKD.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Although the underlying mechanistic pathway that might explain the loss of endothelial barrier function in CKD has been unclear so far, it was suggested that vitamin D deficiency might participate in this uremia‐induced phenomenon 6, 32. Here, we found that vitamin D deficiency induced in our recently developed rat model25 did not aggravate the injury on the aortic endothelial layer caused by CKD.…”
Section: Discussionmentioning
confidence: 53%
“…As kidney function declines, there is a progressive decline of both plasma 25 hydroxyvitamin D (25(OH)D) and 1,25‐dihydroxyvitamin D (1,25(OH) 2 D) concentrations, and of the kidney‐derived protein α‐Klotho, accompanied by secondary hyperparathyroidism and increased fibroblast growth factor‐23 levels 4, 5. These hormonal disturbances occur already in early‐stage CKD and are proposed to a make a notable contribution to the initiation and progression of cardiovascular disease 6, 7. Remarkably, there is limited evidence directly pointing to structural abnormalities and a mechanistic role for the endothelial layer in CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Результати досліджень свідчать про те, що кальци тріол бере участь у численних фізіологічних процесах, активує проліферацію й диференціацію імунних клітин [52,53]. Він також індукує апоптоз неопластичних клітин, пригнічуючи їх поділ [52,53], посилює виділення кателіцидіну й бетадефенсину [51,[54][55][56], модулює діяльність лімфоцитів [51], співвідношення лімфоцитів Th-1 і -2 [51,57], зменшує концентрацію прозапальних цитокінів (IL-1, TNF-α), одночасно збільшуючи кількість протизапальних цитокінів (IL-4, -5 і -10) [51,58], зменшує секрецію реніну, таким чином послаблюючи ренін-ангіотензин-альдостеронову систему [59,60], пригнічує ангіогенез [61][62][63] й позитивно впливає на процеси кальцифікації кровоносних судин [64][65][66][67], стимулює синтез нейротрофічних факторів [68,69] і пригнічує фіброз нирок [70,71]. Дефіцит вітаміну призводить до зменшень секреції інсуліну [72].…”
Section: кальціємічний ефект вітаміну Dunclassified
“…Wykazano, że kalcytriol uczestniczy w licznych procesach fizjologicznych, między innymi wspomaga proliferację i różnicowanie komórek należących do układu immunologicznego [50], indukuje apoptozę komórek nowotworowych i spowalnia ich namnażanie [51,52], nasila produkcję katelicydyny i beta-defensyny [50,[53][54][55], moduluje aktywność limfocytów [50], stosunek limfocytów Th1 do Th2 [50,56], zmniejsza stężenie prozapalnych cytokin (IL-1, TNFα) przy jednoczesnym zwiększeniu stężenia cytokin przeciwzapalnych (IL-4, IL-5, IL-10) [50,57], zmniejsza wydzielanie reniny i w ten sposób redukuje aktywność układu renina-angiotensyna-aldosteron [58,59], hamuje angiogenezę [60][61][62] i korzystnie wpływa na procesy zwapnienia w naczyniach krwionośnych [63][64][65][66], stymuluje syntezę czynników neurotroficznych [67,68], hamuje procesy zwłóknienia w nerkach [69,70], a niedobór witaminy D zmniejsza sekrecję insuliny [71]. Witamina D wykazuje silne działanie immunomodulacyjne [57,72].…”
Section: Działanie Plejotropowe Witaminy Dunclassified